2013
DOI: 10.1890/12-1006.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of grassland plant community composition to spatial vs. temporal variation in precipitation

Abstract: Climate gradients shape spatial variation in the richness and composition of plant communities. Given future predicted changes in climate means and variability, and likely regional variation in the magnitudes of these changes, it is important to determine how temporal variation in climate influences temporal variation in plant community structure. Here, we evaluated how species richness, turnover, and composition of grassland plant communities responded to interannual variation in precipitation by synthesizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
186
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(212 citation statements)
references
References 79 publications
17
186
4
Order By: Relevance
“…It stands to reason that thermophilization may be another emergent community property with a relatively strong sensitivity to climate. Although results tend to be more similar when examining synthetic community properties, in situ temporal variability does not always alter community properties in the same direction as predicted by geographic gradients; for example, the effect of rainy years on species richness does not generally mimic the positive relationship between grassland species richness and precipitation across latitudinal gradients (28,29).…”
Section: Discussionmentioning
confidence: 93%
“…It stands to reason that thermophilization may be another emergent community property with a relatively strong sensitivity to climate. Although results tend to be more similar when examining synthetic community properties, in situ temporal variability does not always alter community properties in the same direction as predicted by geographic gradients; for example, the effect of rainy years on species richness does not generally mimic the positive relationship between grassland species richness and precipitation across latitudinal gradients (28,29).…”
Section: Discussionmentioning
confidence: 93%
“…Predicting ecosystem responses to global change is a fundamental issue in ecology. It has been well documented that the aboveground plant community is sensitive to precipitation change (Cleland et al, 2013;Eskelinen and Harrison, 2015) and N deposition (Stevens et al, 2004;Clark and Tilman, 2008), particularly in arid and semi-arid grassland ecosystems, where water and N are generally considered to be limiting resources (Harpole et al, 2007;Yang et al, 2011;Xu et al, 2012b). A growing body of evidence suggests that higher precipitation increases plant species richness (Bai et al, 2008;Xu et al, 2015b), whereas N fertilization is reported as the main driver of the loss of species richness (Gough et al, 2000;Stevens et al, 2004;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In California, where overall aridity has increased in recent decades (18) and coastal and inland fog have declined dramatically (24,25), aridification is predicted to dominate the effects of climate change on natural vegetation over the coming century (18,19,26). Although directional declines in species richness in western US grasslands in response to long-term drying trends are not yet documented, they may be expected based on evidence that grassland species richness is higher in wetter than drier years, geographical locations, and experimental treatments (27)(28)(29). Seed dormancy, especially by annuals, is likely an important facet of short-term fluctuations in grassland species richness in response to water availability (e.g., ref.…”
mentioning
confidence: 99%